Genome‐wide association analysis of natural variation in seed tocochromanols of barley. Issue 3 (28th September 2020) - Mahalingam, Ramamurthy; Sallam, Ahmad H.; Steffenson, Brian J.; Fiedler, Jason D.; Walling, Jason G.
Abstract: Tocochromanols (tocols for short), commonly called Vitamin E, are lipid‐soluble plant antioxidants vital for regulating lipid peroxidation in chloroplasts and seeds. Barley ( Hordeum vulgare L.) seeds contain all eight different isoforms of tocols; however, the extent of natural variation in their composition and their underlying genetic basis is not known. Tocol levels in barley seeds were quantified in diverse H. vulgare panels comprising 297 wild lines from a diversity panel and 160 cultivated spring‐type accessions from the mini‐core panel representing the genetic diversity of the USDA barley germplasm collection. Significant differences were observed in the concentration of tocols between the two panels. To identify the genes associated with tocols, genome‐wide association analysis was conducted with single nucleotide polymorphisms (SNPs) from Illumina arrays for the mini‐core panel and genotyping‐by‐sequencing for the wild barley panel. Forty unique SNPs in the wild barley and 27 SNPs in the mini‐core panel were significantly associated with various tocols. Marker–trait associations (MTAs) were identified on chromosomes 1, 6, and 7 for key genes in the tocol biosynthesis pathway, which have also been reported in other studies. Several novel MTAs were identified on chromosomes 2, 3, 4 and 5 and were found to be in proximity to genes involved in the generation of precursor metabolites required for tocol biosynthesis. This study provides a valuable resource for barley breeding programs targeting specific isoforms of seed tocols and for investigating the physiological roles of these metabolites in seed longevity, dormancy, and germination.